Azabrendanes IV. Synthesis and characterization of N-(alkyl- and benzylsulfonyl)-exo-2-hydroxy-4-azatricyclo[4.2.1.03,7]nonanes - Kasyan, Lilija I.; Касьян, Лілія Іванівна; Tarabara, Igor N.; Тарабара, Ігор Миколайович; Kasyan, Andrey O.; Касьян, Андрій Олексійович; Okovytyy, Sergiy I.; Оковитий, Сергій Іванович; Tokar, Andrey V.; Токар, Андрій Володимирович; Shishkina, Svetlana V.; Шишкіна, Світлана Володимирівна; et al. (My University, 2007)
exo- and endo-5-Aminomethylbicyclo[2.2.1]hept-2-enes have been obtained from stereoisomeric exo- and endo-5-cyanobicyclo[2.2.1]hept-2-enes and the corresponding sulfonamides were obtained through reaction of amines with methyl-, n-propyl-, n-butyl-, benzyl-, and cyclohexylsulfonyl chlorides. From the stereoisomeric sulfonamides with peroxy acids, various products were obtained: exo-sulfonamides were transformed into epoxy derivatives, and, in contrast, most of the endo-stereoisomers underwent heterocyclization resulting in substituted exo-2-hydroxy-4-azatricyclo[4.2.1.03,7]nonanes. The type of the products obtained did not depend on the type of peroxy acid used (peroxyacetic, peroxyphthalic, and m-chloroperoxybenzoic one). In contrast to other endo-sulfonamides, N-(cyclohexylsulfonyl)-endo-5-aminomethylbicyclo[2.2.1]hept-2-ene in reaction with peroxyacetic acid did not undergo heterocyclization, probably, due to steric factors. The structure and stereochemical homogeneity of the sulfonamides and the structure of the products of their oxidation with peroxy acids were confirmed by spectroscopic methods. The molecular structure of N-(cyclohexylsulfonyl)-endo-5-aminomethyl-exo-2,3-epoxybicyclo[2.2.1]heptane was determined by X-ray diffraction analysis. The mechanism of the intramolecular heterocyclization reaction of N-substituted endo-5-aminomethyl-exo-2,3-epoxybicyclo[2.2.1]heptanes was studied at the BHandHLYP/6-31G(d) level of theory. екзо- та ендо-5-амінометилбіцикло[2.2.1]гепт-2-ени були отримані зі стереоізомерних екзо- та ендо-5-ціанобіцикло[2.2.1]гепт-2-енів, а відповідні сульфаніламіди були отримані реакцією аміни з метил-, н-пропіл-, н-бутил-, бензил- і циклогексилсульфонілхлоридами. Із стереоізомерних сульфонамідів з пероксикислотами були отримані різні продукти: екзосульфонаміди були перетворені в епоксидні похідні, і, навпаки, більшість ендостереоізомерів піддалися гетероциклізації з утворенням заміщених екзо-2-гідрокси-4-азатрицикло[4.2. 1.03,7]нонани. Тип отриманих продуктів не залежав від типу використовуваної пероксикислоти (пероксиоцтової, пероксифталевої, м-хлорпероксибензойної). На відміну від інших ендосульфонамідів, N-(циклогексилсульфоніл)-ендо-5-амінометилбіцикло[2.2.1]гепт-2-ен у реакції з пероксіоцтовою кислотою не піддається гетероциклізації, ймовірно, через стеричних факторів. Спектроскопічними методами підтверджено структуру та стереохімічну однорідність сульфаніламідів, а також будову продуктів їх окиснення пероксикислотами. Методом рентгеноструктурного аналізу визначено молекулярну структуру N-(циклогексилсульфоніл)-ендо-5-амінометил-екзо-2,3-епоксибіцикло[2.2.1]гептану. Досліджено механізм внутрішньомолекулярної реакції гетероциклізації N-заміщених ендо-5-амінометил-екзо-2,3-епоксибіцикло[2.2.1]гептанів на рівні теорії BHandHLYP/6-31G(d).
Азабрендан IV. Синтез і характеристика N -(алкіл- і бензилсульфоніл)- екзо -2-гідрокси-4-азатрицикло[4.2.1.0 3,7 ]нонанів
Keywords: azabrendanes IV; азабрендан IV; synthesis; синтез; characterization; характеристика